2015
DOI: 10.1089/hgtb.2014.096
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Excision of VCP R155H Mutation by Cre-LoxPTechnology as a Promising Therapeutic Strategy for Valosin-Containing Protein Disease

Abstract: Inclusion body myopathy associated with Paget's disease of the bone and frontotemporal dementia is attributed to mutations in the valosin-containing protein (VCP) gene, mapped to chromosomal region 9p13.3-12. Affected individuals exhibit scapular winging and die from progressive muscle weakness and cardiac and respiratory failure in their 40s to 50s. Mutations in the VCP gene have also been associated with amyotrophic lateral sclerosis in 10-15% of individuals with hereditary inclusion body myopathy and 2-3% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…There is insufficient information about the incidence and prevalence, genotype–phenotype correlations, penetrance, natural history and causes of death in IBMPFD. Currently, there is no known specific treatment for IBMPFD, and even though there are some interesting leads from animal studies [46] there are no established patient cohorts and outcome measures to test these compounds/approaches in appropriate clinical trials.…”
Section: Background and Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is insufficient information about the incidence and prevalence, genotype–phenotype correlations, penetrance, natural history and causes of death in IBMPFD. Currently, there is no known specific treatment for IBMPFD, and even though there are some interesting leads from animal studies [46] there are no established patient cohorts and outcome measures to test these compounds/approaches in appropriate clinical trials.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Histologically, the uphill exercised VCP R155H/+ mice displayed an improvement in muscle atrophy, and decreased expression levels of ubiquitin, P62/ SQSTM1 , LC3I/II, and TDP-43 autophagy markers, suggesting an alleviation of disease-induced myopathy phenotypes. In contrast, mice exercised to run downhill did not show any improvement [4]. Targeted excision of the p.R155H mutation in VCP mice using Cre-ER ™ -VCP R155H/+ technology demonstrated improved muscle strength and quadriceps fibre architecture, reduced expression of autophagy markers, reduced brain neuropathology, decreased apoptosis, and improvement of the Paget-like bone changes [4].…”
Section: Session 4 – Vcp Function and Dysfunction: Pre-clinical Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, adenine nucleotide transferase is dysregulated due to pathogenic mutations involving VCP/p97 , resulting in reduced ATP levels [ 20 ]. Utilization of the Cre-LoxP technology for excision of the VCP/p97 R155H missense mutation was anticipated as a correctional approach for this mutation [ 21 ], but currently there are no effective treatments for these genetic mutations.…”
Section: The Vcp/p97 Genementioning
confidence: 99%
“…In vitro analysis of VCP mutants has shown pathologically enhanced ATPase enzymatic activity [ 14 16 ]. Additionally, excision of the mutant allele in the heterozygous mouse model of VCP disease, which contains the most common patient-specific mutation R155H, has been shown to improve the disease pathology [ 17 ]. Recent studies in drosophila models carrying gain of function pathogenic VCP mutations have shown severe mitochondrial fusion defects, and increased degradation of mitofusins (MFN1 and MFN2) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%